A Biopolymer Heparin Sodium Interlayer Anchoring TiO2 and MAPbI3 Enhances Trap Passivation and Device Stability in Perovskite Solar Cells. Issue 22 (18th April 2018) - You, Shuai; Wang, Hui; Bi, Shiqing; Zhou, Jiyu; Qin, Liang; Qiu, Xiaohui; Zhao, Zhiqiang; Xu, Yun; Zhang, Yuan; Shi, Xinghua; Zhou, Huiqiong; Tang, Zhiyong
Abstract: Traps in the photoactive layer or interface can critically influence photovoltaic device characteristics and stabilities. Here, traps passivation and retardation on device degradation for methylammonium lead trihalide (MAPbI3 ) perovskite solar cells enabled by a biopolymer heparin sodium (HS) interfacial layer is investigated. The incorporated HS boosts the power conversion efficiency from 17.2 to 20.1% with suppressed hysteresis and Shockley–Read–Hall recombination, which originates primarily from the passivation of traps near the interface between the perovskites and the TiO2 cathode. The incorporation of an HS interfacial layer also leads to a considerable retardation of device degradation, by which 85% of the initial performance is maintained after 70 d storage in ambient environment. Aided by density functional theory calculations, it is found that the passivation of MAPbI3 and TiO2 surfaces by HS occurs through the interactions of the functional groups (COO −, SO3 −, or Na + ) in HS with undersaturated Pb and I ions in MAPbI3 and Ti 4+ in TiO2 . This work demonstrates a highly viable and facile interface strategy using biomaterials to afford high‐performance and stable perovskite solar cells. Abstract : Incorporating a biopolymer heparin sodium interlayer provides a molecular bridge in between the TiO2 and MAPbI3 layers, which boosts the efficiency in perovskite solar cells up to 20.1% with simultaneously enhanced air‐stability. The retardation of device degradation leads to maintaining >85% of the initial power conversion efficiency after 70 d storage in air.